Development of a Head and Neck Regional Anesthesia Task Trainer for Emergency Medicine Learners - Diane L Gorgas; Sarah Greenberger; Jillian McGrath; David P Way; Chad Donley (eScholarship Publishing, University of California, 2017)
Audience: This innovation is designed for medical students through senior residents. Introduction: Regional anesthesia increases the EM physician's ability to provide effective pain relief and to complete procedures within the Emergency Department (ED). Studies consistently demonstrate that emergency physicians undertreat pain when performing basic procedures such as suturing lacerations.1,2 Regional anesthesia allows for effective pain relief, while avoiding the risks associated with systemic analgesia/anesthesia or the tissue distortion of local anesthesia.3 Knowledge of the anatomy involved in various nerve blocks is crucial to the development of proper technique and successful performance of this skill. Three dimensional (3-D) model simulation-based mastery of procedural skills has been demonstrated to decrease resident anxiety, improve success rates, and decrease complications during the resident's transition into the clinical setting.5,6 Similarly, use of a 3-D head and neck model to practice application of facial regional anesthesia is hypothesized to improve provider confidence and competence which will in turn provide an improved patient experience. Objectives: In participating in the educational session associated with this task trainer, the learner will: 1) Identify landmarks for the following nerve blocks: Infraorbital, Supraorbital (V1), Mental, Periauricular 2) Demonstrate the appropriate technique for anesthetic injection for each of these nerve blocks 3) Map the distribution of regional anesthesia expected from each nerve block 4) Apply the indications and contraindications for each regional nerve block Method: This low-fidelity task trainer allows residents and medical students to practice various nerve blocks on the face in order to improve learner confidence and proficiency in performing facial regional anesthesia.